Emerging role of interaction between m6A and main ncRNAs in gastrointestinal (GI) cancers - Xu, Yating; Yu, Xiao; Guo, Wenzhi; He, Yuting (Frontiers in Immunology, 2023)
As a prevalent epigenetic modification, the role of m6A has been increasingly highlighted in the alteration of numerous RNAs implicated with multiple biological processes, such as formation, export, translation, and degradation. With further the understanding of m6A, accumulating evidence shows that m6A modification similarly affects metabolic process of non-coding genes. But the specifical interplay of m6A and ncRNAs (non-coding RNAs) in gastrointestinal cancers still lacks complete discussion. Thus, we analyzed and summarized how ncRNAs affect the regulators of m6A and by what means the expression of ncRNAs is altered via m6A in gastrointestinal cancers. We focused on the effect of the interaction of m6A and ncRNAs on the molecular mechanisms of malignant behavior in gastrointestinal cancers, revealing more possibilities of ncRNAs for diagnosis and treatment in term of epigenetic modification.